Waning Vaccine Effectiveness Against Influenza-Associated Hospitalizations Among Adults, 2015–2016 to 2018–2019, United States Hospitalized Adult Influenza Vaccine Effectiveness Network. (19th January 2021) - Ferdinands, Jill M; Gaglani, Manjusha; Martin, Emily T; Monto, Arnold S; Middleton, Donald; Silveira, Fernanda; Talbot, H Keipp; Zimmerman, Richard; Patel, Manish
Abstract: We observed decreased effectiveness of influenza vaccine with increasing time since vaccination for prevention of influenza A(H3N2), influenza A(H1N1)pdm09, and influenza B/Yamagata–associated hospitalizations among adults. Maximum vaccine effectiveness (VE) was observed shortly after vaccination, followed by an absolute decline in VE of about 8%–9% per month postvaccination.